Syngas for Internal Combustion Engines, Current State, and Future Prospects: A Systematic Review - Suparmin, Prayudi; Nurhasanah, Roswati; Nelwan, Leopold O.; Salleh, Hanim; Ridwan, Muhammad; Anugerah, M (International journal of automotive and mechanical engineering, 2024)
Biomass is a potential alternative energy source. This study offers a comprehensive analysis of biomass gasification as an energy source, particularly its application in diesel engines, gas engines, and gas turbines. No specific research has been identified that addresses syngas utilization as fuel for internal combustion engines. The paper employs the PRISMA methodology to select and analyze observations. The examination encompasses four subjects: biomass, reactor gasification, operational parameters, and syngas for internal combustion. The Van Krevelen diagram is employed to analyze the characteristics of biomass that produce high-energy syngas, efficiency, variable calorific value of syngas, and decreased power output. Feedstock, gasification reactors, and operational conditions significantly influence the generation of biomass gasification syngas. A downdraft reactor is appropriate for small- to medium-scale gasification. The utilization of biomass gasification technology and syngas as fuel for internal combustion engines is investigated. The hydrogen-to-carbon ratio (H/C), oxygen-to-carbon ratio (O/C), high temperature, low ash content, low equivalence ratio (ER), and the amount of air in the syngas all affect its calorific value. The advantages of utilizing syngas include reduced pollutants, decreased reliance on diesel fuel, and a reduction in diesel fuel use in internal combustion engines. The disadvantages of syngas include necessary engine modifications, decreased thermal efficiency, the calorific value of syngas, and decreased power generation.